Characteristics of Coal and Cleat Attributes in Ulak Lebar and Surroundings Area, Lahat Regency, South Sumatra - Rahmawati, Mutia Armilia; Sari, Siska Linda; Triyoga, Alan; wati, Idar (UIR PRESS, 2018)
The research conducted in Ulak Lebar Area, Lahat Regency, South Sumatra. The focus of this study is on the Muara Enim Formation as it is known as the main coal-bearing formation in South Sumatra Basin. The research is aimed to determine the characteristics of coal based on its physical properties, also knowing the cleat development at the coal seam in the research area. The methods used such as literature study, field observation and laboratory test. Field observations included the observations of coal megascopic appearance and cleat attributes analysis such as the measurements of cleat orientation, aperture, spacing and length. The analysis result of cleat at LP 2A and LP 2B shows a relatively similar such as spacing value ranged between 6 - 9 cm and 5.5 – 8.6 cm while the aperture value ranged from 0.05 - 0.2 cm, and 0.05 - 0.25 cm, whereas at LP 67 the spacing value ranged from 1.5 to 3.3 cm and the aperture valued between 0.1 - 0.3 cm. A rather significant difference between the cleat spacing values of LP 67 towards both previous observation stations is indicated by the geological processes occurred during the coalification process thus affected the development of cleats in coal, the geology structure control is characterized by a relatively large aperture and smaller spacing values. The laboratory test conducted is maceral analysis, shows the coal in the research area is dominantly composed of vitrinite (74,8%) and the vitrinite reflectance value is 0,40 indicating the coal classified as sub-bituminous rank.